Camphor sulfonic acid surfactant assisted polythiophene nanocomposite for efficient electrochemical hydrazine sensor. (26th February 2020) - H, Vijeth; S P, Ashokkumar; Yesappa, L; M, Vandana; Devendrappa, H
Abstract: In this present work, we demonstrate an efficient electrochemical sensor for the detection of hydrazine, using glassy carbon electrode (GCE) modified with camphor sulfonic acid (CSA) assisted polythiophene / aluminium oxide (PTHA) nanocomposite. The CSA-PTHA nanocomposite was synthesised using an in situ chemical oxidative polymerisation method. The nanocomposite was characterised by XPS, AFM, DSC / DTA and impedance analysis. The CSA-PTHA nanocomposite modified GCE can be used for efficient hydrazine electrochemical sensor with high sensitivity and low limit of detection (LOD). The electrochemical detection test of hydrazine was conducted with CSA-PTHA modified GCE by the cyclic voltammetry (CV) and amperometric techniques and the results are compared with pure polythiophene (PTH) modified GCE. Comparing with PTH modified GCE; CSA-PTHA modified GCE illustrates a higher sensing performance leading to significant sensitivity of 0.285 μ A μ M −1 cm −2 and a very low LOD of 0.18 μ M at S/N = 3 for wide linear range of hydrazine concentration from 10 μ M to 90 μ M with a correlation coefficient R 2 = 0.99668. Also, the performance of CSA-PTHA modified GCE electrode is comparable or even better than that of the other reported functional materials for hydrazine detection. Hence, our result shows that the compositing of conducting polymer with metal oxide could offer an efficient way to fabricate advance and economic electrochemical sensors.